Pertanggungjawaban Alokasi Dana Kampung - Apolus Betaubun (Department of State Administration - Musamus University, 2020)
The purpose of this research is to find out how the Responsibility of Village Fund Allocation in Tambat, Tanah Miring District, Merauke Regency. Theoretical Benefits, as reference material for research in the field of future accountability. In discussing and reviewing the issue of implementation, the accountability of village fund allocation in Tambat Tanah Miring District Merauke Regency the author uses a qualitative research method, namely data collection can be from interviews, observation notes, photo taking, audio and video recording. This type of descriptive research is a research that is sought to observe problems systematically accurate funds regarding the facts and characteristics of certain objects, with the number of informants as many as 13 people.The results of this study indicate that the accountability of village fund allocation in the implementation of village funds in Tambat, Tanah Miring District, Merauke Regency, runs well but there are still a number of problems that occur, planning, realization of the program and not in accordance with the details and calculations in the RAB. Kampung, Implementation of Village Fund Allocation conducted by Kampung Tambat Officials has not gone well and has not been carried out in accordance with the procedure because the village head of Tambat was considered not transparent regarding Village Fund Allocation to the people of Tambat Village, Reporting indicators, Village Fund Allocation has not been implemented properly due to reports what has been made is not maximal with what is done in Tambat and indicators, the accountability of the village head regarding the Village Fund Allocation also does not work with planning, implementation and reporting, this is evidenced by the making of the first report and the answer to ADD ADK, PROSPECTS made by other parties not by village officials have not been implemented with the reality that happened at Tambat.